Penerapan roster sebagai pencahayaan dan penghawaan alami pada bangunan - Lestari, Wiji Suci (Maliki Interdisciplinary Journal, 2024)
Natural lighting and natural ventilation are important aspects in a building because with good lighting and ventilation circulation, the rooms in the building will be able to maximize the air that enters so as to cause comfort and health to users. to create buildings with good lighting and ventilation, many materials can be used and applied to buildings. but in order for the aesthetic value to remain visible, it is necessary to choose materials that can function as natural lighting and air conditioning while adding to the aesthetic impression of the building, such as the use of roster materials. over time, the types, colors and shapes of roster are increasingly diverse according to their function. so, each variation of roster type can provide different benefits to the building, especially related to the performance of the facade design and the impact on comfort for users. in connection with the application of roster in buildings, the purpose of the researcher writing this article is to find out how the function of roster is used as natural lighting and ventilation for buildings. the methodology taken in this article is a literature review, which brings together data by studying theories and understanding various literatures related to the topic in this study.